Deductively-inductively - Johnson, Fred (Frederick A.), author; University of Windsor, publisher (Colorado State University. Libraries, 1980)
Johnson separates arguments from acts of arguing and claim that the deductive/inductive distinction belongs with the latter not with the former.
Keywords: logic; argument; deduction; induction